2021
DOI: 10.5194/bg-18-3087-2021
|View full text |Cite
|
Sign up to set email alerts
|

Methane oxidation in the waters of a humic-rich boreal lake stimulated by photosynthesis, nitrite, Fe(III) and humics

Abstract: Abstract. Small boreal lakes are known to contribute significantly to global CH4 emissions. Lake Lovojärvi is a eutrophic lake in southern Finland with bottom water CH4 concentrations up to 2 mM. However, the surface water concentration, and thus the diffusive emission potential, was low (< 0.5 µM). We studied the biogeochemical processes involved in CH4 removal by chemical profiling and through incubation experiments. δ13C-CH4 profiling of the water column revealed a methane-oxidation hotspot just below th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 97 publications
1
23
0
Order By: Relevance
“…Methane being a limiting factor only when oxygen is abundant enough to be potentially inhibiting also suggests that electron acceptors could be a limiting factor for CH 4 oxidation in the lower layers of the studied lakes. This limitation in electron acceptors in CH 4 -rich waters has been suggested by several studies where experimental addition of O 2 or alternative electron acceptors in anoxic water as well as oxygenic photosynthesis have increased CH 4 oxidation rates (Milucka et al, 2015;Oswald et al, 2015Oswald et al, , 2016van Grinsven et al, 2021). Whereas not necessarily related to abundance, these studies showed that the lack of electron acceptors could limit MO metabolism.…”
Section: High Relative Abundance Of Mo In the Meta-and Hypolimnion Has A Complex Relationship With O 2 And Chmentioning
confidence: 61%
“…Methane being a limiting factor only when oxygen is abundant enough to be potentially inhibiting also suggests that electron acceptors could be a limiting factor for CH 4 oxidation in the lower layers of the studied lakes. This limitation in electron acceptors in CH 4 -rich waters has been suggested by several studies where experimental addition of O 2 or alternative electron acceptors in anoxic water as well as oxygenic photosynthesis have increased CH 4 oxidation rates (Milucka et al, 2015;Oswald et al, 2015Oswald et al, , 2016van Grinsven et al, 2021). Whereas not necessarily related to abundance, these studies showed that the lack of electron acceptors could limit MO metabolism.…”
Section: High Relative Abundance Of Mo In the Meta-and Hypolimnion Has A Complex Relationship With O 2 And Chmentioning
confidence: 61%
“…In addition, several gammaproteobacterial genera (e.g., Methylomonas, Methylobacter, Methylomicrobium) have been shown to directly couple methane oxidation to denitrification under O 2 -limiting conditions (Kits et al, 2015b;Cao et al, 2019;van Grinsven et al, 2020a). Recently, stimulation of bacterial methane oxidation rates by iron (III), manganese (IV), and humic compounds has been shown (Oswald et al, 2016;He et al, 2021;van Grinsven et al, 2021) and that certain strains of Methylomonas (Gammaproteobacteria) and Methylosinus (Alphaproteobacteria) can use ferrihydrite minerals as electron acceptors to oxidize methane (Zheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Only eight out of 5569 MAGs analyzed here were predicted to encode machinery for methanogenesis, among only 21 archaeal MAGs that passed the quality cutoffs. This, along with dissolved methane measurements in similar systems (Rissanen et al ., 2021; van Grinsven et al ., 2021), suggests that the majority of methanogenesis is occurring in sediments rather than the water column. The observed correlation between iron and methane, both of which are negatively correlated with dissolved oxygen (DO) (Fig 2B), is unsurprising because methanogenesis occurs typically when available iron and other electron acceptors are in the reduced state and Fe(II) is more soluble than Fe(III).…”
Section: Discussionmentioning
confidence: 99%